2001
DOI: 10.1063/1.1425466
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium interdiffusion studies from hafnium silicate into silicon

Abstract: The interdiffusion of Hf and Si from high-κ gate dielectric candidate (HfO2)1−x(SiO2)x thin films deposited on Si (100) was studied using x-ray photoelectron spectroscopy, time-of-flight secondary ion mass spectrometry, high resolution transmission electron microscopy, and Rutherford backscattering spectrometry in combination with chemical etching. After extreme rapid and conventional furnace thermal annealing treatments, Hf incorporation into Si is limited to less than 0.5–1 nm from the interface. Implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…Furthermore, in agreement with EDS, EELS could not detect any Hf in the interfacial layer. The result is consistent with a previous study showing no substantial Hf diffusion into Si at temperatures below 1000 1C [18].…”
Section: Methodssupporting
confidence: 95%
“…Furthermore, in agreement with EDS, EELS could not detect any Hf in the interfacial layer. The result is consistent with a previous study showing no substantial Hf diffusion into Si at temperatures below 1000 1C [18].…”
Section: Methodssupporting
confidence: 95%
“…The tail of the Hf signal penetrating the Si substrate is a known measurement artifact. [12] In contrast, for thin films (sample F, thickness of 5.6 nm) depth profiling reveal homogenous, but Si-rich layers with a Hf/Si ratio of almost 1:1 after RTA. Taking the Hf/Si ratio of about 6:1 obtained for as-deposited layers into account, additional Si from the substrate has to be incorporated into thin films during RTA.…”
Section: Physical Characterization Of the Filmsmentioning
confidence: 89%
“…Previous studies 1 in other high-k ultrathin films on Si indicated that the interface layer thickness and composition can vary according to the deposition method and routine, and various species can be transported during post deposition thermal processing, like oxygen, 9,10 Si, [11][12][13] and the metal species, 14,15 altering the atomic concentrations as well as chemical composition of the system and consequently electrical characteristics like dielectric constant, interface density of states, and mobility of charge carriers in the transistor channel. In particular, stability against annealing in O 2 -containing atmospheres is of high interest, since in further processing steps it is either performed intentionally to improve leakage current and CET characteristics 1,7,8 or unintentionally, because oxygen is almost always residual in any production furnace.…”
mentioning
confidence: 99%